Tissue-Engineered Vascular Rings from Human iPSC-Derived Smooth Muscle Cells - Biraja C. Dash; Karen Levi; Jonas Schwan; Jiesi Luo; Oscar Bartulos; Hongwei Wu; Caihong Qiu; Ting Yi; Yongming Ren; Stuart Campbell; Marsha W. Rolle; Yibing Qyang (Stem Cell Reports, 2016)
There is an urgent need for an efficient approach to obtain a large-scale and renewable source of functional human vascular smooth muscle cells (VSMCs) to establish robust, patient-specific tissue model systems for studying the pathogenesis of vascular disease, and for developing novel therapeutic interventions. Here, we have derived a large quantity of highly enriched functional VSMCs from human induced pluripotent stem cells (hiPSC-VSMCs). Furthermore, we have engineered 3D tissue rings from hiPSC-VSMCs using a facile one-step cellular self-assembly approach. The tissue rings are mechanically robust and can be used for vascular tissue engineering and disease modeling of supravalvular aortic stenosis syndrome. Our method may serve as a model system, extendable to study other vascular proliferative diseases for drug screening. Thus, this report describes an exciting platform technology with broad utility for manufacturing cell-based tissues and materials for various biomedical applications.